Critical Review On Water Quality Due To Pipe Leakage In Water Distribution System - BASHARUDIN, MUHAMMAD FAIZ; OTHMAN, NORZILA (Recent Trends in Civil Engineering and Built Environment, 2022)
Previous study on pipe leakage in water distribution has been gathered and analyze to identify the characteristic of water from leaking pipe and solve the problem of pipe leakage that will disturb the quality of water. Critical review was carried out by searching for journals on trusted sources such as Scopus and Science Direct to discuss the research findings, including describing the basic features of the component that are related to drinking water quality due to pipe leakage, and VOSviewer software has been used to generate a map based on the relationship between pipe leakage and water quality. Important parameters have been reviewed from previous paper such as BOD level, dissolve oxygen,chlorine and others related to the drinking water quality. Suggestions and recommendations such as sophisticated leak detection techniques and rehabilitation or replacement are proposed in order to improve the quality if water if there is pipe leakage in water distribution systems